A teoria histórico-cultural e a brincadeira : (re)pensando a educação infantil a partir dos autores contemporâneos - Faria, Mariana de Oliveira (2016)
We seek to apprehension, understand and analyze how the game is understood by the Historicalcultural Theory, in the context of Early Childhood Education, from the analysis of the productions of the following contemporary international authors: Marilyn Fleer, Mariane Hedegaard, Seth Chaiklin, Bert Van Oers, Elena Kravtsova and Gennadi Kravtsov. Because it is a theoretical study on the Historical-cultural Theory as well as the theoretical and methodological contributions made by international authors, were analyzed books and articles of the aforementioned authors, therefore the methodology adopted for this research is theoretical and bibliographical. With our analysis, we conclude that to the authors worked, Early Childhood Education should be structured to promote scientific learning of the child, goal of all education, therefore, play, regarded as the dominant activity of the preschool period, must be considered in the space of Early Childhood Education and can contribute to the development of the child. In the development of this work, we focus on the contributions of Marilyn Fleer, to be among the chosen authors, the author who has more discussed the issue of play in the space of Early Childhood Education. Therefore, we hope to contribute to think one Early Childhood Education quality for all walks of life, seeking the comprehensive development of children under five years in their maximum potential, based on the assumptions of Historicalcultu al Theory.